Control of a robotic convoy through path planning and orientation strategies - Giovanni Rodrigo Bermudez-Bohorquez; Christian Anderson Mancipe-Bernal; Joan Emmanuel Ortiz-Velasquez (Revista Científica, 2017)
This paper presents an overview about control methods implemented on robotic convoy systems or cooperative systems on mobile platforms which can be used for path planning, orientation, environment perception, route tracking and control systems in which involve the measurement, analysis, and interpretation of different variables for further implementation. A review was made of investigation articles on bibliographic indexes and databases about control methods used in convoy systems to evidence progress, trends and application methods.